ENHANCED LOCALIZATION SYSTEM BASED ON COSELM, WSRC AND KNN FOR LARGE-SCALE INDOOR SPACES - GAN , HENG YI (2019)
The high accuracy, large coverage, long-lasting stable, fast and easy setup position system is highly demanded in various situations and applications. Currently, the outdoor localization and tracking system relies on the Global Positioning System (GPS) which is a mature technology.